#RhetoricSoEnglishOnly: Decolonizing rhetorical studies through multilingualism. Issue 4 (2nd October 2019) - Sowards, Stacey K.
ABSTRACT: Rhetorical scholarship must move in new linguistic and decolonial directions, to illustrate those languages/cultures/nationalities that have been marginalized in academia. English language dominance in the academy reflects relations of power, race, ethnicity, culture, globalization, colonization, and dualistic ways of thinking. Fluency in English is a type of linguistic capital that is preferred and demanded within academic scholarship in the US and globally. This essay explores what might we consider from other (non-dominant) languages and cultures that would expand our understandings of rhetoric and rhetorical practice, drawing from examples in Indonesian and Spanish. I also examine questions such as: How might concepts in other languages besides English enhance our knowledge and understanding of multicultural rhetorical practices? How are those who are multilingual expected to engage in multilingual work with little recognition for that academic, personal, and emotional labor? The profound impact that language usage has on all of us should be of utmost concern and interest for rhetorical scholars as we seek to understand how audiences connect with rhetorics of all kinds.